Macroeconomic Effects of Sovereign Restructuring in a Monetary Union : A Model-based Approach - Forni, Lorenzo (IMF Working Papers; Working Paper ;, 2013)
We assess the macroeconomic effects of a sovereign restructuring in a small economy belonging to a monetary union by simulating a dynamic general equilibrium model. In line with the empirical evidence, we make the following three key assumptions. First, sovereign debt is held by domestic agents and by agents in the rest of the monetary union. Second, after the restructuring the sovereign borrowing rate increases and its increase is fully transmitted to the borrowing rate paid by the domestic agents. Third, the government cannot discriminate between domestic and foreign agents when restructuring. We show that the macroeconomic effects of the restructuring depend on: (a) the share of sovereign bonds held by residents in the country as compared to that held by foreign residents, (b) the increase in the spread paid by domestic agents and (c) its net foreign asset position at the moment of the restructuring. Our results also suggest that the sovereign restructuring implies persistent reductions of output, consumption and investment, that can be large, in particular if the share of public debt held domestically is large, the private foreign debt is high and the spread paid by the government and the households does increase.